The Network of Environment Hadith Narrators in Sahih al-Bukhari: A Social Network Analysis - Alamsyah, Alamsyah; Dyah, Hapsari Ekonugraheni; Zailani Surya, Marpaung; Abdul, Ghafur; Rudi, Kurniawan (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
This article aims to analyze the social network of ḥadīth narrators and matn ḥadīth which contain environmental messages in the Ṣaḥīḥ al-Bukhārī. This article is the result of an empirical research using a mixed approach (qualitative content analysis and social network analysis). The population of this study is all ḥadīth in the Ṣaḥīḥ al-Bukhārī. The researchers choose 40 environmental ḥadīth purposively as the research samples. The source of research data comes from the Encyclopedia 9 Ḥadīth™ application published by Lidwa Pustaka. The results of the study indicate that the message in environmental ḥadīth could be categorized into several themes such as management of natural resources, both in the livestock, agriculture, mining and forestry sectors, management of water resources, ethics towards the animal, environmental health; personal health; and resource utilization. We identify 40 environmental ḥadīths which narrated by 122 narrators (119 male narrators and three female narrators) who had passed away between 36 H - 252 H, domiciled in 14 cities, from generations of ṣaḥābat, tābi‘īn, and tābi‘ al-tābi‘īn, and having 53 kunyah. The network of environmental ḥadīth narrator has 301 ties with density levels reaching 0.997 and six sub-groups. In this network, the dominant actor was Muhammad b. Muslim b. ‘Ubaydillāh b. ‘Abdullāh b. Shihāb and Mālik b. Anas b. Mālik b. Abī Amir. After Medina, many environmental traditions were narrated by narrators domiciled in Basrah City and Kufah City in Iraq. The researcher discusses the practical and theoretical implications of this finding for ḥadīth research in Indonesia.